Effectiveness of Student Participation in Campus Organizations - Giska Putri Mustaqim; Tri Wahjoedi (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Student participation in campus organizations is a vital aspect of their personal and academic development. Engagement in these organizations enriches students' academic experiences and fosters essential soft skills such as leadership, communication, and teamwork. This study evaluates the effectiveness of student involvement in campus organizations by analyzing various impacts, including academic performance, interpersonal skill development, and readiness for the workforce. Data from multiple sources indicate that students active in campus organizations exhibit higher leadership abilities, better academic performance, and increased employability. However, the study also highlights challenges such as balancing organizational responsibilities with academic commitments. Through a comprehensive literature review by considering relevant books and journals, this research identifies key factors influencing the effectiveness of student participation and provides recommendations for universities to enhance student involvement. Ultimately, the findings underscore the significant role of campus organizations in preparing students for future professional and personal challenges, advocating for institutional support to maximize the benefits of such participation.